ANALISIS PENYEBAB PENGEMBALIAN BERKAS KLAIM RAWAT JALAN DITINJAU DARI SYARAT PENGAJUAN KLAIM DI RSU HERMINA ARCAMANIK - Liasari, Ardia Putri (Jurnal Infokes, 2023)
This study aims to determine the analysis of the causes of returning outpatient claim files in terms of the requirements for submitting claims at RSU Hermina Arcamanik. The method used is a qualitative research method with a descriptive approach. Data collection techniques used are observation, interviews, literature study, and documentation. Sampling in this study was a portion of the verification results claim files in January-March as many as 83 files. From the results of research conducted regarding the causes of returning claims from outpatients, there are problems including: (1) Incomplete filling in of files submitted to BPJS (2) Lack of accuracy of officers in coding (3) Often claim files are lost or piled up due to by the absence of a special place to store claims files that have been processed or those that have not been processed. The suggestions that the author conveys are (1) Improve and improve communication with officers for better performance (2) For nurses and doctors to be more careful in writing patient data and determining disease diagnoses so as to minimize the occurrence of claims being returned (3) Fill in with complete every requirement in the outpatient file (4) Always hold regular meetings and evaluations with related units. Keywords: Claim Returns, Completeness, BPJS Claims